Occurrence of Potential Bacterial Pathogens and Their Antimicrobial Susceptibility Patterns Isolated from Herbal Medicinal Products Sold in Different Markets of Gondar Town, Northwest Ethiopia. (19th May 2016) - Yesuf, Abdela; Wondimeneh, Yitayih; Gebrecherkos, Teklay; Moges, Feleke
Abstract : Background . The World Health Organization estimates that about 80% of the world's population uses herbal medicine to treat various illnesses as means of primary healthcare. However, during preparation, herbal plants may be exposed to contamination by potential pathogens, and this may lead to infections. The aim of this study was to determine bacterial contamination of herbal medicinal products and to assess the antibiotic susceptibility pattern of the isolated bacteria. Methods . A cross-sectional study was conducted from January 1 to May 25, 2013, at Gondar Town. A total of 55 samples used as oral, local, and intranasal routes of administration were collected from the herbalists. Results . In the present study the total aerobic bacterial count ranges from zero to2.41 × 10 9 CFU/g with mean count of1.99 × 10 8 CFU/g or mL while the total coliform count showed an average of1.05 × 10 8 CFU/g or mL with a range of zero to2.1 × 10 9 CFU/g. The most common bacteria isolated were Bacillus spp. followed by Enterobacter spp., Shigella dysenteriae, and Salmonella spp. Multiple drug resistance was not uncommon and it was found that 125 (83.4%) of the isolates were resistant to two or more antibiotics. Conclusion . Herbal medicinal preparations were highly contaminated with pathogenic microorganisms with high microbial load. Most of the isolates have multiple drug resistance. Using those contaminated herbal medicines may lead to infection of other health related risks. Therefore, this warrants urgent training of herbalists and management scale-up for quality and safety of medicinal plants.